Case study of MNC relocation decision process. - Lui, Chris Yui Ho. (2009)
Companies constantly look for ways to improve their competitive advantages over their business rivals. Having a world class manufacturing operation is one of the key advantages that most global corporations use to stay ahead of the competition because it helps them to deliver top-quality products at the lowest operating cost; it also ensures that the marketing division get any new product in the volume that they need and at the lime they want to launch. It is with this constant drive to improve that multinational corporations with manufacturing division periodically evaluate their existing manufacturing facility against available alternatives.